2013
DOI: 10.1111/nph.12437
|View full text |Cite
|
Sign up to set email alerts
|

Defining the selectivity of processes along the auxin response chain: a study using auxin analogues

Abstract: Summary The mode of action of auxin is based on its non‐uniform distribution within tissues and organs. Despite the wide use of several auxin analogues in research and agriculture, little is known about the specificity of different auxin‐related transport and signalling processes towards these compounds. Using seedlings of Arabidopsis thaliana and suspension‐cultured cells of Nicotiana tabacum (BY‐2), the physiological activity of several auxin analogues was investigated, together with their capacity to indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 83 publications
7
40
0
Order By: Relevance
“…However, our receptor binding Efficiency ranking agrees well with previous systems, including those based only on biological activity (Supplementary Table S2) and the recent compilation linking tolerance to, e.g. , 2,4-D and 2,4,5-T with receptor selectivity, 29 adding mechanistic detail.…”
Section: Resultssupporting
confidence: 88%
“…However, our receptor binding Efficiency ranking agrees well with previous systems, including those based only on biological activity (Supplementary Table S2) and the recent compilation linking tolerance to, e.g. , 2,4-D and 2,4,5-T with receptor selectivity, 29 adding mechanistic detail.…”
Section: Resultssupporting
confidence: 88%
“…Our data also showed that oxIAA did not interfere with the accumulation in cells of 2,4-D and NAA, which are known to be good substrates for the plasma membrane-located auxin carriers (Delbarre et al, 1996;Petrášek et al, 2006;Simon et al, 2013). This indicates that oxIAA is not transported via the auxin influx or efflux carriers (Figure 8).…”
Section: Discussionsupporting
confidence: 50%
“…Moreover, SV localization of a member of the AGCVIII kinase family, the action of which is required for PIN activity [30], has not been reported, arguing that PINs in the SVs are possibly inactive [13]. An additional argument that PINs are active at the PM is that increasing PINs incidence at the cell surface, e.g., by inhibiting their endocytosis leads to increased auxin efflux [31,32]. Overall, methods for separate measurement or perturbation of parameters in Equations (48) and (49) are needed to unambiguously distinguish between vesicular-mediated and PM-mediated auxin fluxes.…”
Section: Discussionmentioning
confidence: 99%